2019
DOI: 10.26451/abc.06.03.05.2019
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling Great Apes' Decoy-Effect Bias in a Food Choice Task

Abstract: The decoy effect is a violation of rationality that occurs when the relative preference between two target options changes with the addition of a third option, called the decoy, that is no better than the target options but worse than one of the options on one attribute. The presence of the decoy increases the chance that the option that dominates it on this attribute is chosen over the other target option. The current study tested decoy effects with great apes' food preferences. We presented apes with two tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…For instance, an agent may remember that two actions result each on a typical amount of and kind of food, and if forced to choose, compares the predicted consequences of the two actions in terms of two dimensions, amount and palatability, to rank them. This framework is often invoked to argue that some violations of economic rationality occur because different dimensions are given different weights when constructing preference at the time of choice (for examples, see Bateson et al 2003 ; Nachev et al 2021 ; Sánchez-Amaro et al 2019 ).…”
Section: On the Concept Of Utilitymentioning
confidence: 99%
“…For instance, an agent may remember that two actions result each on a typical amount of and kind of food, and if forced to choose, compares the predicted consequences of the two actions in terms of two dimensions, amount and palatability, to rank them. This framework is often invoked to argue that some violations of economic rationality occur because different dimensions are given different weights when constructing preference at the time of choice (for examples, see Bateson et al 2003 ; Nachev et al 2021 ; Sánchez-Amaro et al 2019 ).…”
Section: On the Concept Of Utilitymentioning
confidence: 99%
“…Experimental research investigating the influence of how choices are framed can help elucidate primates' risk aversion and decision-making strategies (Lakshminarayanan et al, 2011;Proctor et al, 2014). Even when relatively complete information is provided, individuals' choices may be affected by the presence of a "decoy," or distractor element that pulls a subject's attention away from the target (and potentially better) options (e.g., Sanchez-Amaro et al, 2019).…”
mentioning
confidence: 99%
“…But in primates, the only study 95 that has found a decoy effect used a perceptual discrimination task [25], 96 but the same monkeys do not show the effect when choosing among tasks 97 that vary in effort required [26]. Further, two studies using food choice 98 tasks, which are arguably most similar to the foraging experiments used 99 with bees and grey jays, found no evidence of this bias [19,27]. One 100 possibility for these results is that the primates' preferences between the 101 initial options were too strong for the decoys to change their behavioural 102 choices, even though they might have changed the perceived value of the 103 options.…”
Section: Introduction 64mentioning
confidence: 99%
“…in part, explain why previous studies using food preference paradigms 246 with primates [19,27] have found mixed results, because they used the 247 same food items and quantities for each individual. In this study, we 248 carefully calibrated monkeys' initial preferences 1) by changing the food 249 items and sizes and 2) by using a countable food item that does not easily 250 substitute for fruit and vegetable pieces.…”
mentioning
confidence: 99%